Activation of serotonergic system with fluoxetine or 5-HTP restores blunted hypercapnic ventilatory response in Parkinson’s disease model - Kryspin Andrzejewski; Magdalena E. Orłowska; Małgorzata Zaremba; Ilona Joniec-Maciejak; Katarzyna Kaczyńska (Scientific Reports)
Abstract The main symptoms of Parkinson’s disease (PD) affect physical movement, but are often associated with a wide range of non-motor symptoms, as well as breathing disorders. Of these, respiratory muscle weakness, decreased air passage resulting in restrictive breathing changes, respiratory rhythm abnormalities, and upper airway dysfunction are usually indicated. To study respiratory impairment in PD, we used a rat model of PD induced by bilateral injection of 6-hydroxydopamine (6-OHDA) into the striatum. We investigated the ventilatory response to hypercapnia (HCVR) and the phenomenon of phrenic long-term depression (pLTD). To determine the effect of serotonergic system activation on HCVR we used fluoxetine, a selective serotonin reuptake inhibitor (SSRI), and 5-hydroxy-L-tryptophan (5-HTP), a precursor of serotonin (5-HT) synthesis. Treatment with both serotonergic agents did not affect air breathing in 6-OHDA and sham rats, while the impaired HCVR in the PD model was restored to the values present in the control group. Moreover, we also showed that pLTD was fully expressed only in sham rats. The 6-OHDA rats showed significantly reduced pLTD, indicating a disruption in the brainstem structures that regulate this phenomenon. The changes in respiration were accompanied by a significant reduction in striatal dopamine levels and a smaller but significant reduction in serotonin concentration in the striatum and brainstem shown by HPLC analysis. Our results indicate a possible degeneration of the serotonergic system in this model, which may have influenced the impairment of HCVR and pLTD. Activation of the serotonergic system eliminating blunted HCVR indicates its potential in alleviating respiratory distress.